The extrinsic and intrinsic apoptotic pathways are involved in manganese toxicity in rat astrocytoma C6 cells - Alaimo, Agustina (2011)
Manganese (Mn) is a trace element known to be essential for maintaining the proper function and regulation of many biochemical and cellular reactions. However, chronic exposure to high levels of Mn in occupational or environmental settings can lead to its accumulation in the brain resulting in a degenerative brain disorder referred to as Manganism. Astrocytes are the main Mn store in the central nervous system and several lines of evidence implicate these cells as major players in the role of Manganism development. In the present study, we employed rat astrocytoma C6 cells as a sensitive experimental model for investigating molecular mechanisms involved in Mn neurotoxicity. Our results show that C6 cells undergo reactive oxygen species-mediated apoptotic cell death involving caspase-8 and mitochondrial-mediated pathways in response to Mn. Exposed cells exhibit typical apoptotic features, such as chromatin condensation, cell shrinkage, membrane blebbing, caspase-3 activation and caspase-specific cleavage of the endogenous substrate poly (ADP-ribose) polymerase. Participation of the caspase-8 dependent pathway was assessed by increased levels of FasL, caspase-8 activation and Bid cleavage. The involvement of the mitochondrial pathway was demonstrated by the disruption of the mitochondrial membrane potential, the opening of the mitochondrial permeability transition pore, cytochrome c release, caspase-9 activation and the increased mitochondrial levels of the pro-apoptotic Bcl-2 family proteins. In addition, our data also shows for the first time that mitochondrial fragmentation plays a relevant role in Mn-induced apoptosis. Taking together, these findings contribute to a deeper elucidation of the molecular signaling mechanisms underlying Mn-induced apoptosis. © 2011 Elsevier B.V. All rights reserved.